Use of multi-walled carbon nanotubes (mwcnts) in medium density fiberboard to increase the fire retardancy - Dineshkumar, Gunasagaran (2014)
Medium Density Fiberboard (MDF) is known as wood composite which are extensively used in furniture manufacture and building construction. In such application enhanced resistance to flame spread is considered as an advantage. The properties of MDF boards can be improved with the use of flame retardant chemicals. As a potential solution, Multi-walled Carbon Nanotubes (MWCNTs) will be used as flame retardant in MDF due to its good thermal properties and stability. Urea formaldehyde (UF) will be used as a binder to bind all the wood fibers. Flame retardant properties of the boards were investigated by IS 1734-1 to 20 (1983): Methods of test for plywood [CED20: Wood and other Lignocellulosic products] standard. The physical and mechanical properties including Thickness Swelling (TS), Internal Bond (IB) and Modulus of Rupture (MOR) of the samples were determined. The TS, MOR and IB tests were conducted as per ASTM D 1037 standard. Throughout the experiment, MDF boards treated with 2.5 wt% MWCNTs showed good fire retardant properties compared to Control board and 1.0wt% + MDF boards. The mechanical and physical properties improved significantly when MWCNTs were added to boards. From the DSC and TGA graph, it can be seen that the thermal conductivity and thermal stability of the samples, based on MWCNTs, were higher than control samples. Furthermore, the FTIR and XRD analysis proved that the presence of MWCNTs in the MDF samples. This research study will be useful in providing an effective way to increase the fire retardancy and as well as mechanical and physical properties of MDF board.